Pedagogical significance of methods in the educational process - Komilova Kimyoxon, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Recently, the issue of using innovative technologies in working with children has been increasingly raised in education. Teacher today faces new challenges and new opportunities open up, taking into account their application.